Synthesized evaluation of various injection regimens on hydrogen propelled homogeneous charge compression ignition and dual fuel modes for an automotive application - Sathishkumar, S.; Ibrahim, M. Mohamed (International journal of hydrogen energy, 2023)
The present work aimed to perform a comparative study between the hydrogen diesel homogeneous charge compression ignition (HDHCCI) and hydrogen diesel dual fuel (HDDF) modes with multiple injection regimens. The results showed that the maximum feasible hydrogen energy shares (HES) were 73.99% and 27.46% for the HDDF and HDHCCI modes in a single pulse injection. The level of efficiency increased while increasing HES in the HDHCCI mode for any injection regimen. Conversely, the level of efficiency decreased on increasing HES for the HDDF mode, however it yields higher efficiency than the HDHCCI mode at a steady HES operation. The extremely low NO emission was attained using single pulse and twin pulse HDHCCI modes as compared with HDDF mode, and vice versa for smoke and HC emissions, since the existence of cool flame due to too early injection timings drastically altered the combustion characteristics of HDHCCI mode. •Maximum energy share limits to 73% and 27% for HDDF and HDHCCI modes.•A portion of low temperature combustion influences less on HDDF mode.•Wall-impingement significantly affects the combustion of HDHCCI mode than HDDF mode.•Injection regimens drastically impact the characteristics of HDHCCI and HDDF modes.•Triple pulse and twin pulse improve the performance of HDHCCI and HDDF modes.